Analysis of the clinical impact of NPM1 mutant allele burden in a large cohort of younger adult patients with acute myeloid leukaemia. (8th October 2019) - Linch, David C.; Hills, Robert K.; Burnett, Alan K.; Russell, Nigel; Gale, Rosemary E.
Summary: Although an NPM1 mutation is generally considered to be a good prognostic marker in acute myeloid leukaemia, it has recently been suggested that a higher level of NPM1 mutant ( NPM1 MUT ) alleles relative to wild‐type alleles is associated with poor clinical outcome. We therefore sought to confirm this finding in a larger study of 876 NPM1 MUT cases entered into UK national trials. In univariate analysis, the higher NPM1 MUT allele burden was associated with a lower complete remission (CR) rate, higher relapse rate and reduced overall survival, but this was largely attributable to the association of the higher NPM1 MUT allele burden with other known poor risk factors, particularly the presence of a concomitant FLT3 internal tandem duplication. In multivariate analysis, there was no significant impact of the NPM1 MUT allele burden on CR rates, and the impact on relapse and overall survival, whilst still significant, was greatly reduced. This impact was similar in patients who did or did not receive an allogeneic transplant in first CR. We conclude that the binary presence or absence of an NPM1 mutation, combined with minimal residual disease levels following induction therapy, should continue to be used in therapeutic management rather than stratification according to the NPM1 MUT level.